An examination and evaluation of YTU library and documentation building in terms of building biology - Balanlı, Ayşe; Öztürk, Ayşe; Karabiber, Zehran; Unver, Rengin; Gedik, Gülay; Yavuz, Güner; Vural, Müjdem S. (Elsevier, 2006)
The physical and social characteristics of internal and external environments of the YTU Library Building were examined and the results were compared with the required levels and standards. Negative characteristics which may cause health problems on temporary and permanent users were determined, and potential health risks due to those characteristics were identified.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Building biology; University library building; Physical environment; Social environment; Indoor environment; Health problems